Sex-Biased miRNAs in the Gonads of Adult Chinese Alligator (Alligator sinensis) and Their Potential Roles in Sex Maintenance - Hu, Meng-Yuan; Yu, Jun; Lin, Jian-Qing; Fang, Sheng-Guo (Frontiers in Genetics, 2022)
MicroRNA (miRNA) is a category of single-stranded non-coding small RNA (sRNA) that regulates gene expression by targeting mRNA. It plays a key role in the temperature-dependent sex determination of Chinese alligator (Alligator sinensis), a reptile whose sex is determined solely by the temperature during the incubation period and remains stable thereafter. However, the potential function of miRNAs in the gonads of adult Chinese alligators is still unclear. Here, we prepared and sequenced sRNA libraries of adult female and male alligator gonads, from breeding (in summer) and hibernating (in winter) animals. We obtained 130 conserved miRNAs and 683 novel miRNAs, which were assessed for sex bias in summer and winter; a total of 65 miRNAs that maintained sex bias in both seasons were identified. A regulatory network of sex-biased miRNAs and genes was constructed. Sex-biased miRNAs targeted multiple genes in the meiosis pathway of adult Chinese alligator oocytes and the antagonistic gonadal function maintenance pathway, such as MOS, MYT1, DMRT1, and GDF9. Our study emphasizes the function of miRNA in the epigenetic mechanisms of sex maintenance in crocodilians.